(untitled) (Revista de História da UEG (REVHIST), 2021)
Our article aims to present how the Instituto Mises Brazil has performed conceptual interpretations in order to defend the free market and private ownership. We use as examples two concepts: socialism and libertarianism. We will make a brief exposition of the work in the introduction, present some characteristics of Digital History and Immediate History and then explain how Instituto Mises Brazil’s strategy of spreading ideas works, how this procedure shows a transnational performance, which partners are linked to Instituto Mises Brazil and the interpretations practiced about the two terms. As a conclusion, we observe that the concept of socialism has been associated with state policies and always from an economic point of view, disregarding other conceptions. In the case of libertarianism, it was interpreted as an ideology that preached the right to individual freedom and private property, rejecting the interpretation made by left-wing libertarian groups, such as anarchism. These interpretations were used to strengthen the ideology propagated by the Institute: defense of private ownership and free market. Keywords: Socialism. Libertarianism. Private Ownership. Free Market.